KEANEKARAGAMAN ALGA EPILITIK DI SUMBER AIR PANAS BUKIK GADANG KECAMATAN LEMBANG JAYA KABUPATEN SOLOK - Anggraini, Devi; Risdawati, Renny; Nursyahra, Nursyahra (Pendidikan Biologi, 2013)
Epilitic algae is part of a group microperifitic algae that lives attached to the substrate (stone,coral, gravel and other hard objects). Solok Regency has Talang Mount with the beautifulnatural that can be enjoyed, this place also has a hot water source in Bukik Gadang, NagariKoto Anau, Lembang Jaya District, Solok Regency which is believed has a power to heal ortreat and as a tourism object. The temperature of hot water is about 39 â 45 ÂºC. The researchof epilitic algae in Bukik Gadang hot spring, Lembang Jaya District, Solok Regency in haddone Desember 2012 â Maret 2013. The purpose of this research to know the variety ofepilitic algae at different temperatures. This research has done by using a descriptive surveymethod with determining three station based on the different temperatures and sampling wasdone by purposive sampling at each station were taken three points. This research found 17species of epilitic algae consist of two classes of Bacillariophyceae and Cyanophyceae. Theclass Bacillariophyceae found 9 species and class Cyanophyceae 8 species that live attemperatures of 39 â 45 ÂºC, pH 7,01 â 7,50, dissolved oxygen 1,44 â 3,96 mg/l, the sulfurcontent from 0,089 â 0,105 mg/l.